2004
DOI: 10.1063/1.1791638
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional simulations of magnetic reconnection in slab geometry

Abstract: Magnetic reconnection in an incompressible plasma in three-dimensional slab geometry has been studied through magnetohydrodynamics numerical simulations. Particular attention has been paid to the case in which several unstable modes that correspond to resonant surfaces in different positions of the simulation domain, are excited at the beginning of the simulation. The dynamical evolution of such a system leads to a behavior different than what is expected from the linear theory. In particular the effects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
40
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 17 publications
10
40
0
Order By: Relevance
“…The outer region of the wave-vector space results is deprived of magnetic energy. A similar behavior was also observed by Onofri et al, 27 although in their simulations, an enlargement was observed of the anisotropy angle, which has not been observed in our simulations. One reason could be the fact that our simulations stop earlier than those of Onofri and collaborators.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…The outer region of the wave-vector space results is deprived of magnetic energy. A similar behavior was also observed by Onofri et al, 27 although in their simulations, an enlargement was observed of the anisotropy angle, which has not been observed in our simulations. One reason could be the fact that our simulations stop earlier than those of Onofri and collaborators.…”
Section: Discussionsupporting
confidence: 70%
“…As observed also by Onofri et al, 27 most of the energy is confined along a given direction, highlighted with the dashed line. The slope of this line is given by the condition k z = ±k x and corresponds to the resonance condition k · B 0 =0.…”
Section: -7supporting
confidence: 58%
See 3 more Smart Citations